Analisis Mengenai Pengaturan Sanksi terhadap Pelanggaran Pencatatan Perkawinan di Indonesia - Nofitasari, Solehati (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2022)
Marriage registration as regulated in Article 2 paragraph (2) of the Marriage Law, although it has been socialized for quite a long time, it turns out that until now there are still perceived obstacles. The pros and cons became even more pointed, when one of the articles in the bill that became controversial was the punishment imposed on the perpetrators of unregistered marriages. The method in this study uses a normative legal research method, with a statutory approach. Regulations applied by the State of Indonesia have regulated the application of sanctions for violations of marriage registration in their respective countries, but with some important notes; First, when it comes to regulations and also in terms of material content: Regulations in Indonesia are contained in Government Regulation (PP) No. 9 of 1975 Article 45 paragraph (2) letter b. Second, based on the history of the establishment of the regulation on Family Law, which includes sanctions for violating marriage registration: Regulations in Indonesia have regulated marriage since 1946, namely in Law 22 of 1946 concerning the Registration of Marriage, Marriage, Divorce and Reconciliation.